2015
DOI: 10.1155/2015/195328
|View full text |Cite
|
Sign up to set email alerts
|

An Open-Label Uncontrolled, Multicenter Study for the Evaluation of the Efficacy and Safety of the Dermal Filler Princess VOLUME in the Treatment of Nasolabial Folds

Abstract: The dermal filler Princess VOLUME is a highly cross-linked, viscoelastic hyaluronic acid injectable gel implant used for aesthetic treatment. To evaluate the efficacy and safety of Princess VOLUME in the treatment of nasolabial folds, an open-label uncontrolled, multicenter study was conducted. Forty-eight subjects were recruited who had moderate to deep wrinkles, according to the Modified Fitzpatrick Wrinkle Scale (MFWS). Subjects received Princess VOLUME in both nasolabial folds at Day 0. Nasolabial fold sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…The observed decrease in improvement between Week 24 and Week 36 is in line with published data on the longevity of HA fillers of about 4 to 12 months 10 . Comparing the maintenance of the improvement of NLFs with results of a previous investigation using the HA filler Princess VOLUME, the equivalent device but without lidocaine hydrochloride in the formulation, 8 results confirm the reports demonstrating that the addition of lidocaine has no effect on the longevity of the dermal filler 5 …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The observed decrease in improvement between Week 24 and Week 36 is in line with published data on the longevity of HA fillers of about 4 to 12 months 10 . Comparing the maintenance of the improvement of NLFs with results of a previous investigation using the HA filler Princess VOLUME, the equivalent device but without lidocaine hydrochloride in the formulation, 8 results confirm the reports demonstrating that the addition of lidocaine has no effect on the longevity of the dermal filler 5 …”
Section: Discussionsupporting
confidence: 89%
“…The subjects' rating of satisfaction showed high and consistent satisfaction with the result of the treatment. Subjects rated their appearance independent of the investigator's GAIS assessment as “very satisfied” in 85.2% of subjects at Week 4, 78.7% at Week 24, and 79.0% at Week 36; these results conform to the GAIS scores, and to results of the investigation of Princess VOLUME (an equivalent product but without lidocaine in the formulation) 8 …”
Section: Discussionsupporting
confidence: 53%
“…were obtained in a study in which nasolabial folds were treated with PV and observed over 270 days. 5 The literature data from long-term studies on similar devices are in line with these observations. 6,8 Prolongation of the effect can also be facilitated by an additional touch-up at later time points (ie, at 12 and 24 months).…”
Section: Discussionsupporting
confidence: 73%
“…Even after the longer follow‐up time of nine months, the positive treatment effect was still evident in well above 60% of patients attending this final visit. Comparable results were obtained in a study in which nasolabial folds were treated with PV and observed over 270 days 5 . The literature data from long‐term studies on similar devices are in line with these observations 6,8 .…”
Section: Discussionsupporting
confidence: 64%
“…Taken together, these results were consistent with results of previous investigations using the HA Fillers, Princess ® FILLER, the equivalent device but without lidocaine hydrochloride, and Princess ® VOLUME, the equivalent device but with a higher dynamic viscosity. In these investigations, the use of the Princess ® fillers was highly successful in the treatment of facial lipoatrophy, morphological asymmetry and debilitating scars (Princess ® FILLER) and in the treatment of NLFs (Princess ® VOLUME) over a 6-month period, as judged by investigators, subjects, and independent reviewers 1517. All ADEs that were reported in this investigation (ie, injection site hematoma, pain, and swelling) were mild or moderate, transient, and are commonly reported following treatment with dermal fillers 18…”
Section: Discussionmentioning
confidence: 99%